Public Health Ethics in Times of Crisis: The Experience of the Quebec Public Health Ethics Committee During the COVID-19 Pandemic - Désy, Michel; Leclerc, Bruno; St-Pierre, Julie (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The aim of this text is to share the experience of the Quebec Public Health Ethics Committee (CESP) during the COVID-19 pandemic, and more specifically on the risks and opportunities faced during that time. In particular, we discuss the agility of the CESP, conferred by its operating rules and structured ethical review process, and its resulting ability to react quickly to address the ethical issues raised by public health interventions in times of crisis. Our focus is on the challenges that come with the CESP’s autonomy, specifically its capacity to address critical ethical concerns in a timely manner.